2022
DOI: 10.3390/v14051066
|View full text |Cite
|
Sign up to set email alerts
|

Duplex One-Step RT-qPCR Assays for Simultaneous Detection of Genomic and Subgenomic RNAs of SARS-CoV-2 Variants

Abstract: A hallmark of severe acute respiratory syndrome virus (SARS-CoV-2) replication is the discontinuous transcription of open reading frames (ORFs) encoding structural virus proteins. Real-time reverse transcription PCR (RT-qPCR) assays in previous publications used either single or multiplex assays for SARS-CoV-2 genomic RNA detection and a singleplex approach for subgenomic RNA detection. Although multiplex approaches often target multiple genomic RNA segments, an assay that concurrently detects genomic and subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(60 reference statements)
1
1
0
Order By: Relevance
“…In view of our data, we have demonstrated that using our assays in a multiplex format did not affect the analytical parameters. Additionally, these parameters were similar to those from other assays recently developed in our laboratory for the detection of canine enteric viruses and feline respiratory pathogens [ 69 , 70 ]. In this study, two to three log 10 improvement of the LOD 95 was determined when compared to the previously published multiplex PCR assays for the detection of CAdV-2, CDV, CIV, and CPiV [ 38 ].…”
Section: Discussionsupporting
confidence: 74%
“…In view of our data, we have demonstrated that using our assays in a multiplex format did not affect the analytical parameters. Additionally, these parameters were similar to those from other assays recently developed in our laboratory for the detection of canine enteric viruses and feline respiratory pathogens [ 69 , 70 ]. In this study, two to three log 10 improvement of the LOD 95 was determined when compared to the previously published multiplex PCR assays for the detection of CAdV-2, CDV, CIV, and CPiV [ 38 ].…”
Section: Discussionsupporting
confidence: 74%
“…This is consistent with previous work reporting that N1 and N2 were the sequence features of SARS-CoV-2 most likely to be recovered from wastewater [ 37 ]. We also found subgenomic Orf3a in abundance in one wastewater sample, a subgenomic RNA for which RT-qPCR assays [ 55 ] are also available, demonstrating the ability of wastewater sequencing to detect such RNA molecules. While looking at the mean coverage of the first 300 nucleotides on the 5′-end of the genome, we found that most samples directly collected from aircraft had this region covered (5 out of 6), while only 4 out of 10 samples had reads covering these regions in samples obtained from water tanks pooled from various sources.…”
Section: Discussionmentioning
confidence: 82%